Deregulated immune cell recruitment orchestrated by FOXM1 impairs human diabetic wound healing - Andrew P. Sawaya (Nature Portfolio, 2020)
Diabetic foot ulcers (DFU) represent a complex disease with limited treatment options. Here, the authors compare human RNASeq patient data from DFU, oral mucosa and skin acute wounds, identifying FOXM1 as a mediator of macrophage and neutrophil recruitment, which contributes to disease pathogenesis and is dysregulated in patients.